2017
DOI: 10.1080/0886022x.2017.1398665
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced plasma ACE and ACE2 level in the uremic patients with cardiovascular diseases and its change during a single hemodialysis session

Abstract: Pathogenically imbalanced circulating ACE/ACE2 was detected in the HD patients, particularly those with CVD. HD session could increase ACE/Ang II/AT1R axis and decrease ACE2/Ang-(1-7)/Mas axis activity in the circulation of HD patients with CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
0
18
1
1
Order By: Relevance
“…Likewise, uremic patients under chronic haemodialysis exhibited an increase in ACE and Ang II plasmatic levels, whereas ACE2 and Ang (1–7) levels were lower when compared to controls [ 90 ]. That imbalanced ACE/ACE2 ratio was more severe in the haemodialysis patients with cardiovascular disease.…”
Section: Comorbidities and Ace/ace2 Balance Disruptionmentioning
confidence: 99%
“…Likewise, uremic patients under chronic haemodialysis exhibited an increase in ACE and Ang II plasmatic levels, whereas ACE2 and Ang (1–7) levels were lower when compared to controls [ 90 ]. That imbalanced ACE/ACE2 ratio was more severe in the haemodialysis patients with cardiovascular disease.…”
Section: Comorbidities and Ace/ace2 Balance Disruptionmentioning
confidence: 99%
“…Further studies of cellular angiotensin-converting enzyme 2 expression in patients on maintenance hemodialysis could explain this effect since decreased angiotensin-converting enzyme 2 activity has been reported in this population. [5][6][7] SUPPLEMENTARY MATERIAL Supplementary File (PDF) Table S1. Demographics, comorbidities and presentation of the cohort.…”
Section: Treatment Impact On Covid-19 Evolution In Hemodialysis Patientsmentioning
confidence: 99%
“…Further studies of cellular angiotensin-converting enzyme 2 expression in patients on maintenance hemodialysis could explain this effect since decreased angiotensin-converting enzyme 2 activity has been reported in this population. 5 , 6 , 7 …”
mentioning
confidence: 99%
“…Reduced ACE2 shifts the balance in the RAS toward the Ang II/AT1 Raxis, resulting in the progression of cardiometabolic dysfunction. 41,42 We showed that CRP dose-dependently increases the expressions of ACE, AngII and AT1R proteins, but inhibits ACE2 expression in both adipocytes and VSMCs, suggesting the detrimental effect of CRP on vasculatures is connected with an imbalance of RAS. Ang II/ATR1 signalling also leads to the activation of several downstream kinase pathways, such as extracellular signal-regulated kinases (ERK)1/2.…”
Section: Discussionmentioning
confidence: 90%